Renaissance music in the Slavic World, eds. Marco Gurrieri, Vasco Zara, Turnhout 2019 - Chemotti, Antonio (Muzyka, 2021)
Recenzja książki: Renaissance music in the Slavic World, red. Marco Gurrieri, Vasco Zara, Turnhout 2019